Model of the cascade thermoelectric cooling devices in the mode of the largest energy efficiency - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2016)
We developed and analyzed a model of the interrelation between the reliability indicators of the cascade thermoelectric coolers that operate under regime of the largest energy effectiveness at the serial electrical connection of cascades and the design and energy indicators of cooler. It is demonstrated that the application of cascade thermoelectric devices, built on the basis of standardized modules, is predetermined not only by attaining maximal possible level of cooling but by the increase in efficiency as well. In this case, it is important to obtain maximally possible energy effectiveness at the assigned temperature drop, to select current regime at the assigned design of cooler and to estimate reliability indicators. We obtained ratios for determining the optimum magnitude of relative operating current, which corresponds to the maximum value of refrigerating coefficient of the cooler with the assigned design and temperature drop. They are functional dependences, which connect basic parameters of the two-cascade thermoelectric coolers of the assigned design with relative operating current of the first cascade in the form of algebraic equations of the 4th degree. The conducted analysis of the model demonstrated that there is an optimum ratio of the number of thermoelements in the cascades, which corresponds to the maximum refrigerating coefficient at the assigned temperature drop. The obtained ratios make it possible to determine both the basic parameters and the reliability indicators of the cascade thermoelectric cooler of the assigned design. This provides the possibility to evaluate the efficiency of functioning and prediction of the indicators of reliability in the regime of maximum energy effectiveness under varied conditions of operation.